UnMarketing : stop marketing. Start engaging - Stratten, Scott (Hoboken, N.J. : Wiley, 2012)
Potential and current customers want to be listened to, validated, and have a platform to be heard--especially online. This book shows marketers how to create a mindset and systems that perpetually attract the right customers.
Hierachy of buying -- A word on experts -- Trust gap -- Restaurant that didn't get it -- Cold calling -- Aiming your company at the bottom of the barrel -- Pull and stay -- Reasons why companies don't use social media -- Social media (social currency as well) -- Twitter versus Facebook versus LinkedIn versu Google+ -- Socal media platforming -- HARO: platforming example -- The game has changed: immediacy and relevancy -- Publicized customer service -- Don't bank on the bold -- Seven deadly social media sins -- How Twitter changed my business -- Tassimo -- Local Twitter -- Domino's: word of mouth, mouths are moving ... -- Naked pizza -- Don't feed the trolls -- Tweetathon -- YOur website: old school versus new school -- Captchas -- Experience gap -- RAising and keeping the bar high: Cirque -- Stirring coffee -- Experince gap for small biz -- Using stop start continue -- Zappos -- Rockport -- FreshBooks -- Why you can't learn from millionaires -- Transparency and autheticity -- My transparency on Twitter -- Your transparency on Twitter -- Affiliates -- Testimonials -- Best sellers -- Why being a work-at-home mom is bad for business -- Hello? Walmart? -- Idea creation -- Idea delivery -- Doing in-person seminars -- Tele-seminars -- Tele-summits -- How and why I created a summit ebook instead -- Viral marketing -- Uncercover UnMarketing -- Putting it into practice -- Lush -- Trade shows -- Social media at trade shows -- UnNetworking: why networking events are evil -- The awesomeness of being a 2.0 author -- The UnTour -- The UnEnd.
Includes index.
Keywords: Relationship marketing; Viral marketing